2018
DOI: 10.1029/2018gl077252
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of a High Arctic Glacier to Melt and Runoff Variations

Abstract: The dynamic response of High Arctic glaciers to increased runoff in a warming climate remains poorly understood. We analyze a 10-year record of continuous velocity data collected at multiple sites on Nordenskiöldbreen, Svalbard, and study the connection between ice flow and runoff within and between seasons. During the melt season, the sensitivity of ice motion to runoff at sites in the ablation and lower accumulation zone drops by a factor of 3 when cumulative runoff exceeds a local threshold, which is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 66 publications
2
18
1
Order By: Relevance
“…A related issue is the seasonal dynamical adjustment of ice speed during the start of the ablation period, due to the decrease of basal friction. The use of continuous GPS on Svalbard glaciers (Vieli et al, 2004;Dunse et al, 2012;Vallot et al, 2017;Van Pelt et al, 2018) has confirmed the relation between water supply and ice speed-ups observed elsewhere (Iken et al, 1983;Iken and Bindschadler, 1986).…”
Section: New Challengessupporting
confidence: 53%
“…A related issue is the seasonal dynamical adjustment of ice speed during the start of the ablation period, due to the decrease of basal friction. The use of continuous GPS on Svalbard glaciers (Vieli et al, 2004;Dunse et al, 2012;Vallot et al, 2017;Van Pelt et al, 2018) has confirmed the relation between water supply and ice speed-ups observed elsewhere (Iken et al, 1983;Iken and Bindschadler, 1986).…”
Section: New Challengessupporting
confidence: 53%
“…The average annual and summer (JJAS) temperatures in the period 2011-2017 were −1.6 • C and 4.3 • C respectively, whilst in 2012 annual temperature was higher (−1.1 • C) but summer temperatures were lower (3.6 • C). Higher summer temperature after 2012 would cause more intense melting and faster flow of Hansbreen, as glacier velocity is mostly controlled by the distribution and pressure of water at the glacier bed [63][64][65], which facilitate basal sliding [66][67][68].…”
Section: Closing a Mass Budget Of Hansbreenmentioning
confidence: 99%
“…CC BY 4.0 License. -Berger et al, 2019), central Svalbard (e.g., Van Pelt et al, 2012Vega et al, 2016;Marchenko et al, 2017b;Van Pelt et al, 2018) and on an idealized Svalbard glacier (Van Pelt et al, 2016b). In this study, the model is applied for the first time to the whole of Svalbard.…”
Section: Validation Datamentioning
confidence: 99%